Redirection of CD4+ and CD8+ T lymphocytes via a novel antibody‐based modular targeting system triggers efficient killing of PSCA+ prostate tumor cells. Issue 13 (22nd July 2014) - Arndt, Claudia; Feldmann, Anja; Töpfer, Katrin; Koristka, Stefanie; Cartellieri, Marc; Temme, Achim; Ehninger, Armin; Ehninger, Gerhard; Bachmann, Michael
<x xml:space="preserve">Abstract</x> BACKGROUND There is still a need for new therapeutic options against prostate cancer. Conventional single‐chain bispecific antibodies (bsAbs), that directly cross‐link T cells and tumor cells, hold great potential for efficient tumor treatment. However, rapid development of novel bsAbs is hampered by laborious optimization to improve their efficacy and reduce potential side effects. To accelerate the development of a novel antibody tool for the redirection of T cells to different tumor‐associated antigens, we recently introduced a modular targeting system. METHODS We here describe a novel modular system for treatment of prostate cancer by retargeting of T cells to the prostate stem cell antigen (PSCA). Functionality of the novel PSCA‐specific modular system was investigated in vitro by T cell activation and chromium release assays as well as in immunodeficient mice. RESULTS Similar to a conventional bsAb CD3‐PSCA, the novel PSCA‐specific modular system induces activation of both CD4+ and CD8+ T cells leading to secretion of pro‐inflammatory cytokines and highly efficient target‐specific tumor cell lysis. The novel TM was ready‐to‐use from the time point of construction and functional at low E:T ratios and picomolar concentrations without further optimization. In addition, the PSCA‐specific modular system delays outgrowth of s.c. tumors in mice comparable to bsAb CD3‐PSCA. CONCLUSIONS We have developed a novel PSCA‐specific modular system which triggers an efficient T cell‐mediated killing of PSCA+ tumor cells in vitro and in vivo. The new Ab‐based targeting strategy can functionally replace conventional bsAbs and allows a flexible redirection of T cells to different tumor‐associated antigens. Prostate 74: 1347–1358, 2014. © 2014 Wiley Periodicals, Inc.